Patterns of Corporate Criminalization as Perpetrators of Environmental Crimes in Nickel Mining - Anis Rifai; Aurora Jillena Meliala (UNIFIKASI : Jurnal Ilmu Hukum, 2022)
This study discusses the main issues: first, what is the pattern of punishment for corporations that commit environmental crimes. Related to laws and regulations, in general, laws related to this issue are administrative law and criminal law. First, administrative law related to the concept of pollution and environmental damage by corporations and administrative sanctions. Second, criminal law related to the environment, including corporate criminal acts in the environmental field as stipulated in the criminal provisions of Law Number 32 of 2009 concerning Environmental Protection and Management. The urgency of criminal responsibility for corporations as perpetrators of environmental crimes is because corporate criminal acts in the environmental sector have widespread and complex negative impacts so that they not only cause direct harm to society and the environment but also disrupt the country's financial and economic stability, given the The environmental crimes are committed with economic motives. The pattern of sentencing against corporations that commit environmental crimes in the PPLH Law should contain provisions related to sentencing patterns based on environmental conservation which include aggravation of criminal fines, regulation of the implementation of criminal fines, and sanctions for remedial action due to criminal acts.